Pemberian Mulsa Organik dan Pemangkasan Cabang Terhadap Pertumbuhan Dan Hasil Tanaman Semangka (Citrullus vulgaris Schard) Varietas F1 Punggawa - Gisela Jeanca Betra; Heti Herastuti; Tutut Wirawati (Program Studi Agroteknologi INSTIPER, 2022)
Watermelon (Citrullus vulgaris Schard) is a horticultural commodity rich in nutrients that are beneficial to human health. One of the efforts to increase watermelon productivity is by applying organic mulch and pruning the branch. This research was held in July-October 2022 at the Garden of the Faculty of Agriculture, Universitas Pembangunan Nasional